The life and reign of Queen Elizabeth - Willard, Mary Elizabeth (My University, 1895)
Introduction: Elizabeth, the second Queen Regent of England, born at Greenwich Palace, September seventh, fifteen hundred and thirty-three, was a daughter of King Henry VIII and Anne Boleyn; she was three years old when her mother met her shameful death, and Elizabeth was branded with illegitimacy, and for some time suffered neglect. She owed the thanks for the thoughtful judicious training received in childhood, to her nurse, Lady Brian, a relative of Queen Anne Boleyn. The first public exercise which Elizabeth attended was the Christening of her step brother, Edward, when she was four years old. Her father allowed her to keep company with Edward, and the two shared one another’s studies and became very affectionate, Edward always calling Elizabeth his sweetist sister. When Elizabeth was but sixteen years old she admired Admiral Seymour, and could he have obtained permission of the council they would probably have been married. When in fifteen hundred and forty-nine he was arrested for high treason Elizabeth as well as her servants were arrested and subjected to a severe examination by the council. It was a severe crisis in the life of the Princess, with no maternal friend to advise her, and when she was released she labored faithfully to efface from the minds of the people the memory of her indiscretion; nor was her labor in vain for by her assumption of a grave and sedate demeanor, her plain dress, and the special attention which she paid to theology, she established a reputation for piety and learning, and when seventeen years old, she was pointed out as a model for all young ladies at court.
Citation: Willard, Mary Elizabeth. The life and reign of Queen Elizabeth. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: History; Queen Elizabeth; Theses; Manuscripts (documents)